Pembelajaran Klasikal dalam Menghafal Surat-Surat Pendek Dan Do’a Harian di TPQ Masjid Nurul Jannah Karangrejo Metro Utara - Asy’ari, Hasyim (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine the benefits of classical learning in memorizing the Qur'an at TPQ Nurul Jannah Mosque, Karangrejo Metro Utara by using the theory of multiple movements. This research is a qualitative descriptive research conducted at the TPQ of Nurul Jannah Mosque Karangrejo. The subjects of this research are Ustadz and students. Data collection techniques used are observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, drawing conclusions. Then check the validity of the data done using triangulation technique. The results showed: (a) classical learning is able to provide learning that is easily accepted by students so that they are able to memorize the Qur'an, (b) by applying classical learning at the TPQ Nurul Jannah Mosque, Karangrejo Metro Utara. Ustadz easily teach memorization such as the Koran, reading prayers, (c) with the implementation of classical learning at the TPQ Masjid Nurul Jannah Karangrejo North Metro learning becomes fun and becomes conducive to learning in class so that students learn from ancient times and are able to memorize the memorization given by the ustadz or chaplain.